2022
DOI: 10.3389/fimmu.2022.941492
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative IgE-levels specific for respiratory allergens as biomarker to predict efficacy of anti-IgE-based treatment of severe asthma

Abstract: Molecular therapies, including anti-IgE, biologicals and small molecules are increasingly used for treatment of asthma. The effectiveness of these therapies may be increased with biomarkers. Aim of this study was to assess the value of measuring cumulative IgE levels specific for respiratory allergens to increase the efficacy of anti-IgE therapy for severe bronchial asthma. One hundred and thirty seven patients with severe asthma were recruited from 2016 to 2022. Standard empirical allergy diagnosis (i.e., ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…We found no association between serum IgE concentrations and anti-IgE effectiveness. Consistent correlations between anti-IgE treatment response and baseline total serum IgE or antigen-specific IgE concentrations are lacking ( 52 , 53 ), although recently use of cumulative IgE levels has been suggested ( 54 ). When patients were stratified post-hoc by T2 biomarkers, exacerbations were reduced to a greater degree in those with the presence of both modestly elevated IgE and T2 biomarkers, despite similar IgE concentrations ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found no association between serum IgE concentrations and anti-IgE effectiveness. Consistent correlations between anti-IgE treatment response and baseline total serum IgE or antigen-specific IgE concentrations are lacking ( 52 , 53 ), although recently use of cumulative IgE levels has been suggested ( 54 ). When patients were stratified post-hoc by T2 biomarkers, exacerbations were reduced to a greater degree in those with the presence of both modestly elevated IgE and T2 biomarkers, despite similar IgE concentrations ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is a chronic complicated airway disease, and presents a high prevalence throughout the world (Naumova et al, 2022). Airway inflammation in asthma can be subdivided in T2-high and T2-low subsets based on molecular mechanism (Halayko et al, 2021;Maggi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Li et al 19 showed that the changes in total serum IgE levels may help evaluate responses to omalizumab treatment. Naumova et al 31 provided evidence that measuring cumulative levels of IgE specific for respiratory allergens serve as biomarker to enhance the success of IgE-targeted therapy. However, in our study, we did not find the baseline IgE level to predict the response to omalizumab; similar to the preliminary bioinformatics analysis results from a study by ourselves.…”
Section: Discussionmentioning
confidence: 99%